Ethics assessment in research proposals adopting CRISPR technology - Hirsch, Francois (Array, 2019)
The rapid and exponential growth of genome editing has posed many challenges for bioethics. This article briefly explains the nature of the technique and the particularly rapid development of Clustered Regularly Interspaced Short Palindromic Repeat (CRISPR) technology. The international and, specifically, European-level systems for assessing the ethical issues consequent on these developments are outlined and discussed. The challenges posed by cases in China are summarized to raise concerns about how a more shared, universally consistent appraisal of bioethical issues can be promoted.